Glucose-6-Phosphate Dehydrogenase and Neurospora Morphology - Scott, W. A. (1970)
In addition to the Neurospora crassa mutant col-2, mutations in two other unlinked genes, balloon and frost, lead to distinct morphological growth and abnormal glucose-6-phosphate dehydrogenases. The glucose-6-phosphate dehydrogenases from these strains have increased thermolabilities, altered kinetic parameters, and distinctive electrofocusing patterns. The altered enzyme segregates with each morphological phenotype in crosses to wild type, and there is a correlation between the severity of the enzymic defect and the degree of morphological abnormality in heterocaryons and double mutants. These results are compatible with the hypotheses that the balloon, frost, and col-2 genes are structural genes for glucose-6-phosphate dehydrogenase and that the pleiotropic effects of these altered dehydrogenases are responsible for the mutant morphologies.